(untitled) (Bangladesh Journal of Botany, 2022)
The genetic variability and character association among important yield and attributing traits was studied in 20 genotypes of tomato. The magnus of the phenotypic coefficient of variation (PCV) for all characteristics was higher than the magnitude of the genotypic coefficient of variation (GCV). High PCV, GCV, and heritability accompanied by high genetic advance as per cent of mean was recorded for the number of fruits per plant, average fruit weight, number of flower clusters/plant, number of fruits per cluster, plant height, number of flowers per cluster and locule number, polar diameter, equatorial diameter, pericarp thickness, fruit yield/plant. Therefore, selection in early generations would be effective in the improvement of these traits. The trait inter-relationship studies revealed that for aiming at high-yielding tomato genotypes, selection based on average fruit weight, number of fruits per plant, polar and equatorial diameter, plant height, number of primary branches, days to 50% flowering, and days to the first harvest would be effective. Bangladesh J. Bot. 51(4): 747-757, 2022 (December)